2018
DOI: 10.1021/acs.jpclett.8b01562
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Water-Soluble Highly Fluorescent Low-Dimensional Host–Guest Supramolecular Polymers: Structure and Energy-Transfer Dynamics Revealed by Polarized Fluorescence Spectroscopy

Abstract: Water-soluble, highly fluorescent host-guest chromophore-cucurbit[8]uril supramolecular polymer bundles are investigated by polarized time-resolved photoluminescence spectroscopy, structural methods, and quantum chemistry to fully reveal structural organization and heterogeneity but, in particular, energy-transfer dynamics, being of crucial importance for the design of supramolecular artificial light-harvesting systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 73 publications
(150 reference statements)
0
17
0
Order By: Relevance
“…Further insights on the cascade energy transfer could be obtained from time‐resolved anisotropy studies (Figure 4 g–i). In general, the loss of anisotropy of organized donors within an assembly occurs either through rotational motion or energy migration [16, 30] . In n ‐decane, depolarization through rotational motion is less favored as spontaneous nucleation assists the formation of 2D assemblies and hence energy migration can be the possible pathway for depolarization [16, 30] .…”
Section: Resultsmentioning
confidence: 99%
“…Further insights on the cascade energy transfer could be obtained from time‐resolved anisotropy studies (Figure 4 g–i). In general, the loss of anisotropy of organized donors within an assembly occurs either through rotational motion or energy migration [16, 30] . In n ‐decane, depolarization through rotational motion is less favored as spontaneous nucleation assists the formation of 2D assemblies and hence energy migration can be the possible pathway for depolarization [16, 30] .…”
Section: Resultsmentioning
confidence: 99%
“…This was early realized, [ 15 ] and viscosity studies have indeed demonstrated a significant effect on excited state deactivation of various dyes, [ 20,58 ] stilbene, [ 59 ] and TPE compounds; [ 61–63 ] for structures, see Scheme 1. Thus, in rigid matrixes, as for instance in supramolecular host–guest systems, [ 46–49,68–70 ] stilbenoid compounds become highly luminescent. Therefore, a useful way to distinguish between intramolecular and intermolecular contributions to SLE is the use of solid solutions, e.g., by embedding molecules in polymethylmethacrylate (PMMA; at very low dilutions), as it was done, e.g., for DCS compounds.…”
Section: Molecular Luminescence—intramolecular Processes and Environmental Controlmentioning
confidence: 99%
“…[16,30] In n-decane,d epolarization through rotational motion is less favored as spontaneous nucleation assists the formation of 2D assemblies and hence energy migration can be the possible pathway for depolarization. [16,30] At 3 10 À4 M, 1 in n-decane exhibited an initial anisotropy value (r 0 )of0.25 and reached the plateau region (r 1 )at0.13 by losing the anisotropy with ad ecay time, t r = 45 ps (Figure 4h). The r 0 value of 0.25 at around zero time indicates that the initial orientation of the transition dipole moments has an angle of 308 8.…”
Section: Chemiementioning
confidence: 99%